A novel and practical method to add video monitoring to tilt table testing. - Lange, Frederik Jorrit de; Hofland, Willem Petrus Merijn Emmanuël; Ferrara, Alessio; Gargaro, Alessio; Brignole, Michele; Dijk, Jan Gerrit van; de Lange, Frederik Jorrit; van Dijk, Jan Gerrit (EP: Europace, 2023)
Aims: We describe a novel, practical, and inexpensive method to add video recording during tilt table testing (TTT): Open-Access-Video-TTT.Methods and Results: The Open-Access-Video-TTT set-up uses a personal computer (PC) to capture screen video data from a non-invasive-beat-to-beat (NIBTB) haemodynamic blood pressure (BP) device, combined with video recording of a patient, using Open Broadcaster Software (OBS®). The new Open-Access-Video-TTT set up was tested with both the Finometer (model Finapres Nova®, Medical Systems, the Netherlands) and the Task Force® Touch Cardio monitor (CNSystems, Austria). For this, the Finapres Nova® was enabled in 'remote' mode and Real Video Network Computing (RealVNC®) was installed on the PC/laptop. The Task Force® has a DisplayPort (DP) port, for which a DP/ high-definition multimedia interface (HDMI) cable and a video capture card is used to merge the signals to the PC/laptop. With this method the combined images are stored as a new video signal. TTT can be performed with any routine protocol.Conclusions: Open Access-Video-TTT worked well for both the Finapres NOVA® and the Task Force Monitor ®. This novel method can be used easily by all physicians who wish to add video recording during TTT who do not have access to an electroencephalogram machine.